When Mother Earth Begged for Research: An Indexation of Social and Environmental Hotspots - Tineke Elisabeth Lambooy; Bart Jansen; Martine Bosman (Universitas Airlangga, 2019)
This editorial paper is an introduction to the special Yuridika edition about the ‘Sustainable Market Actors for Responsible Trade’ project (SMART). SMART identifies the areas in which companies and other market players can realise their unfulfilled potential to contribute in their own way to development friendly, environmentally friendly, and socially sustainable business, trade, and investment. SMART creates more awareness on how nondevelopment policies and regulations reinforce or undermine EU development policies. The research presented in this special Yuridika edition aims to find these legal means to reduce the gap between law and reality. In this Editorial, the various contributions to this special edition of the journal Yuridika will be introduced